The diagnosis of socioemotional skills. A look from the aesthetic dimension in early childhood - Marzo Forbes, Nancy Aleida; López Mejías, Modesta; Román Santana, Wanda Marina (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The containment measures established during the COVID-19 pandemic increased interest in socio-emotional skills and their presence in people, mainly in early childhood children. In this sense, the present investigation proposed to evaluate, through artistic activities, the presence of socio-emotional skills in preschool children. In this way, the study was carried out from a qualitative approach with a descriptive design that aimed to diagnose the state of socio-emotional skills in early childhood children. In this way, assessments were established about the level of development achieved in skills such as: self-regulation, empathy, and resilience, which led to the reflection of experiences with teachers to incorporate effective actions with a view to improvement, all through educational techniques aimed at the child and his family. This aspect denoted the need to generate spaces related to emotional education due to its great relevance.